Functional interplay between antagonistic bacteria and Rhizoctonia solani in the tomato plant rhizosphere - Solanki, Manoj Kumar; Solanki, Anjali Chandrol; Rai, Shalini; Srivastava, Supriya; Kashyap, Brijendra Kumar; Divvela, Praveen Kumar; Kumar, Sudheer; Yandigeri, Mahesh S.; Kashyap, Prem Lal; Shrivastava, Alok Kumar; Ali, Baber; Khan, Shahid; et al. (Frontiers in Microbiology, 2022)
Microbial interactions with plant roots play an imperial role in tomato plant growth and defense against the Rhizoctonia solani. This study performed a field experiment with two antagonistic bacteria (Pseudomonas and Bacillus) inoculated in healthy and Rhizoctonia solani treated soil in tomato rhizosphere to understand the metabolic pattern and microbial function during plant disease suppression. In the present study, we assessed soil and microbial enzymes, bacterial and fungal cell forming unit (CFU), and carbon utilization profiling through Bio-Eco plates of rhizoplane samples. Antagonist bacteria and pathogen interaction significantly (p<0.05) influenced the bacterial count, soil enzymes (chitinase and glucanase), and bacterial function (siderophore and chitinase production). These results indicated that these variables had an imperial role in disease suppression during plant development. Furthermore, the metabolic profiling showed that carbon source utilization enhanced under fruit development and ripening stages. These results suggested that carbon sources were essential in plant/pathogen/antagonist interaction. Substrates like β-methyl-D-glucoside, D-mannitol, D-galacturonic acid, N-acetyl-D-glucosamine, and phenylethylamine strongly connect with the suppuration of root rot disease. These carbon sources may help to propagate a healthy microbial community to reduce the pathogen invasion in the plant root system, and these carbon sources can be used as growth stimulators of antagonists against pathogens in the future.